Metafora “Meja Makan” sebagai Upaya Membangun Toleransi di Tengah Kehidupan Masyarakat Indonesia Yang Majemuk - Mariani Harmadi (Sekolah Tinggi Teologi Intheos Surakarta, 2019)
Abstract. The plurality of Indonesian society became a potential conflict that endangers the life of the nation and state if it was not managed properly. For this reason tolerance became an important attitude in living together. This article aimed to review efforts in buliding tolerance in the life of a pluralistic society. Through literature review it was descripted that tolerance could be built through a philosophy rooted in the local culture of Indonesian society. The